MicroRNAs as Regulators of Immune and Inflammatory Responses: Potential Therapeutic Targets in Diabetic Nephropathy - Zhou, Hong; Ni, Wei-Jian; Meng, Xiao-Ming; Tang, Li-Qin (Frontiers in Cell and Developmental Biology, 2021)
Diabetic nephropathy (DN) is the principal cause of end-stage renal disease and results in high morbidity and mortality in patients, causing a large socioeconomic burden. Multiple factors, such as metabolic abnormalities, inflammation, immunoregulation and genetic predisposition, contribute to the pathogenesis of DN, but the exact mechanism is unclear, and the therapeutic strategies are not satisfactory. Accordingly, there is an unmet need for new therapeutic targets and strategies for DN. MicroRNAs (miRNAs) act as major epigenetic mechanisms that regulate gene expression and provide novel insights into our understanding of the molecular and signalling pathways that are associated with various diseases, including DN. Studies in the past decade have shown that different miRNAs affect the progression of DN by modulating different aspects of immune and inflammatory responses. Therefore, in this review, we summarized the pivotal roles of miRNAs in inflammatory and immune processes, with an integrative comprehension of the detailed signalling network. Additionally, we discussed the possibilities and significance of these miRNAs as therapeutic targets in the treatment of DN. This review will facilitate the identification of new therapeutic targets and novel strategies that can be translated into clinical applications for DN treatment.